Differential expression of BMP inhibitors gremlin and noggin in Hydra suggests distinct roles during budding and patterning of tentacles. Issue 12 (9th September 2020) - Krishnapati, Lakshmi Surekha; Khade, Samiksha; Trimbake, Diptee; Patwardhan, Rohan; Nadimpalli, Siva Kumar; Ghaskadbi, Surendra
Abstract: Background: Mechanisms regulating BMP and Wnt pathways and their interactions are not well studied in Hydra . Results: We report identification of BMP inhibitor gremlin, comparison of its expression with that of noggin and possible antagonism between Wnt and BMP signaling in Hydra . Gremlin is expressed in body column with high levels in budding region and in early buds. Noggin, on the other hand, is expressed in the hypostome, base of tentacles, lower body column, and basal disc. During budding, noggin is expressed at the sites of tentacle emergence. This was confirmed in ectopic tentacles in polyps treated with alsterpaullone (ALP), a GSK‐3β inhibitor that leads to upregulation of Wnt pathway. RT‐PCR data show that upregulation of Wnt is accompanied by downregulation of bmp 5‐8b though noggin and gremlin remain unaltered till 24 hours. Conclusions: Different expression patterns of gremlin and noggin suggest their roles in budding and patterning of tentacles, respectively. Further, bmp 5‐8b inhibition by activated Wnt signaling does not directly involve noggin and gremlin in Hydra . Our data suggest that Wnt/BMP antagonism may have evolved early for defining the oral‐aboral axis, while the involvement of BMP antagonists during axial patterning is a recent evolutionary acquisition within the Bilateria lineage. Key Findings: Gremlin is predominantly expressed during budding. Noggin expression is specifically associated with tentacle formation. Wnt activation leads to bmp5‐8b downregulation in hydra. Noggin and gremlin are not directly involved in bmp5‐8b inhibition by activated Wnt signalling.